Molecular Identification Validates Morphological Identification of Javanese Cardamom from Banyumas in Central Java, Indonesia - Sukarsa, Sukarsa; Herawati, Wiwik; Mohamad, Alkhader Ali Mokhaer (Biosaintifika: Journal of Biology & Biology Education, 2024)
Cardamom is one of the prominent plants with significant economic value in the Banyumas Regency, Central Java, Indonesia. Although Javanese cardamom is traditionally categorized under Amomum compactum, the morphological variations observed create ambiguity about its exact species status. DNA barcoding using the maturase K (matK) and ribulose-bisphosphate carboxylase (rbcL) genes is proven as a reliable technique to elucidate the taxonomic status of morphological variable plant cultivars. This study aimed to characterize cardamom from Banyumas Regency using morphological and molecular approaches for taxonomic status identification and genetic diversity evaluation. The matK and rbcL genes were selected as genetic markers and sequenced using a bidirectional sequencing technique. Morphological examination showed significant color variations at the cardamom stem base. All samples had high genetic identities to reference species in databases and were supported by high query cover and zero e-values. Therefore, molecular characterization, alongside geographic distribution assessment, established that this plant belongs to a single species, Amomum compactum. Additionally, the analysis conducted showed a low level of genetic diversity, as evidenced by haplotype and nucleotide diversity. Low-level genetic diversity provides additional data to convince that cardamon in Banyumas Regency belongs to a single species. These results are essential data in seed selection for further cultivation.